Using Triple‐Helix‐Forming Peptide Nucleic Acids for Sequence‐Selective Recognition of Double‐Stranded RNA. Issue 1 (8th September 2014) - Hnedzko, Dziyana; Cheruiyot, Samwel K.; Rozners, Eriks
Abstract: Non‐coding RNAs play important roles in regulation of gene expression. Specific recognition and inhibition of these biologically important RNAs that form complex double‐helical structures will be highly useful for fundamental studies in biology and practical applications in medicine. This protocol describes a strategy developed in our laboratory for sequence‐selective recognition of double‐stranded RNA (dsRNA) using triple‐helix‐forming peptide nucleic acids (PNAs) that bind in the major grove of the RNA helix. The strategy developed uses chemically modified nucleobases, such as 2‐aminopyridine (M ), which enables strong triple‐helical binding under physiologically relevant conditions, and 2‐pyrimidinone (P ) and 3‐oxo‐2, 3‐dihydropyridazine (E ), which enable recognition of isolated pyrimidines in the purine‐rich strand of the RNA duplex. Detailed protocols for preparation of modified PNA monomers, solid‐phase synthesis, HPLC purification of PNA oligomers, and measuring dsRNA binding affinity using isothermal titration calorimetry are included. Curr. Protoc. Nucleic Acid Chem . 58:4.60.1‐4.60.23. © 2014 by John Wiley & Sons, Inc.